Diagnosis and treatment of hepatoid gland adenocarcinoma in a dog: Case report - Engelsdorff, João; Vebber Pessel, Murilo; Braga Brancher, Giovana (Pubvet, 2022)
Adenocarcinoma of the hepatoid glands is a malignant tumor originating from the sebaceous glands that most commonly affects male, senile and intact dogs. The aim of this work is to report the case of an adenocarcinoma of the hepatoid glands in a fourteen-year-old Cocker Spaniel canine. The patient had three ulcerated and infected nodules in the perianal region, the largest being 2,2cm and the smallest 1,0cm in diameter. The patient underwent a surgical procedure to remove the nodules, in which no complications of greater complexity were observed. The results of the fine needle aspiration cytology exam were not compatible with the histopathology, concluding that a compatibility between these two methods is not always observed.
Keywords: Canine; circum-anal; neoplasm; perianal